2015
DOI: 10.12691/ajphr-3-2-7
|View full text |Cite
|
Sign up to set email alerts
|

Child Healthcare in Nepal: Progress and Direction

Abstract: Health policy changes in Nepal displayed struggles against a poor political, geographical, and economic setting; Millennium Development Goal #4 demanded improved infant and child mortality, as well as adequate measles vaccine coverage by the year 2015. Research in this report presents progress and direction of child health care policy across more than a decade of time in attempts of attaining MDG #4 and general child health care advancements. Subsequent observations and suggestions were delineated and offered.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…It's in the Quran." 74 Abe's dreams of establishing a worldwide Islamic caliphate are eerily similar to the current goal of ISIS, and once again, play upon American fears. Akhtar's Pulitzer Prize-winning play ends with a tragic silence and no redeemable Muslim character standing on the stage.…”
mentioning
confidence: 91%
“…It's in the Quran." 74 Abe's dreams of establishing a worldwide Islamic caliphate are eerily similar to the current goal of ISIS, and once again, play upon American fears. Akhtar's Pulitzer Prize-winning play ends with a tragic silence and no redeemable Muslim character standing on the stage.…”
mentioning
confidence: 91%
“…Nepal currently ranks 110th on the United Nations Development Programme's Gender Inequality Index [1], with caste and ethnicity continuing to be major determinants of poverty, education and health outcomes [2][3][4][5]. There are signi cant inequalities in access to and utilisation of basic health services between urban and rural areas, as well as between lowland, hill and mountain zones [2,3,[5][6][7]. This presents a signi cant challenge for Nepal in terms of promoting social and economic development, meeting the Sustainable Development Goals to end preventable deaths of newborns and children under 5 years of age, and achieving universal health coverage.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, individual patient records cannot easily be investigated for health outcome correlations with gender, ethnicity and caste [7]. For the same reason, there is a signi cant data gap that prevents monitoring and evaluation of the practices of front-line health workers, such as the extent to which they comply with treatment guidelines [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The common causes of maternal mortality are hemorrhage, sepsis, unsafe abortions, and labor related complications [8]; for children under five years of age, common causes include respiratory infections, malnutrition, diarrheal diseases, and intrapartum related complications [9]. Even though there has been a remarkable decline in the maternal and under-five mortality ratios since the 1990s [3,10], disparities, depending on geographical areas [11], socio-economic status, educational background, and ethnicity, still exist [3]. In addition, it has been reported that delays in vaccination timings increase the risk of mortality [2,12].…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce these disparities and make timely health care available to all, several community-based, decentralized programs have been implemented throughout the country since the mid-1990s [10,11,13]. Several initiatives have been taken on by the Government of Nepal (GoN) to scale up the existing health care services in collaboration with international organizations.…”
Section: Introductionmentioning
confidence: 99%